Peran Mahasiswa Dalam Meningkatkan Kesehatan Jasmani Masyarakat Desa Padang Panjang Dalam Kegiatan Gotongroyong Dan Senam Pagi Bersama - Alfiqri, A. Chaltren Surya; Martiani, Martiani (Jurnal Kewirausahaan & Inovasi, 2024)
In UNIVED students' Community Service Program (KKN) activities, gotong royong and morning exercises are two important aspects that support physical health. Through gotong royong, students engage in physical activities together with the local community, such as cleaning the environment or undertaking infrastructure projects. Gotong royong not only improves physical fitness, but also builds social bonds and mental well-being among students and the community. Morning exercise, as a routine activity, provides an opportunity for students to improve their fitness with movements that include stretching, aerobics, and strength training. In addition to the physical benefits, morning exercises also play a role in stimulating mental health and providing a positive spirit throughout the day. The combination of gotong royong and morning exercises in the context of UNIVED KKN creates a well-rounded experience, not only aiding community development but also improving physical health and overall well-being.